Implementasi P5 (Projek Penguatan Profil Pelajar Pancasila) Melalui Tema Kewirausahaan di SMP Negeri 5 Kota Bengkulu - Faula Ayustina; Desy Eka Citra Dewi; M. Ilham Gilang (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to describe the implementation of the Pancasila Student Profile Strengthening Project (P5) through the entrepreneurship theme at SMP Negeri 5 Kota Bengkulu and to identify its supporting and inhibiting factors. P5 is a program within the Merdeka Curriculum that emphasizes project-based learning to foster 21st-century skills and character, which include the dimensions of faith, global diversity, cooperation, independence, critical thinking, and creativity. This research employed a descriptive qualitative method with data collected through interviews, observations, and documentation. The findings reveal that the implementation of P5 was systematically carried out in planning, implementation, and evaluation stages. In the entrepreneurship theme, students were engaged in designing, producing, and marketing cassava chips. These activities enhanced entrepreneurial skills while also promoting independence, creativity, collaboration, and responsibility. The main supporting factors included strong leadership commitment, teacher creativity, availability of simple facilities, and involvement of parents and the local community. On the other hand, inhibiting factors identified were limited teacher training, a short project duration, minimal production resources, and the absence of standardized evaluation instruments. Overall, the implementation of P5 through the entrepreneurship theme successfully provided meaningful learning experiences that not only strengthened students’ understanding of entrepreneurship but also integrated Pancasila values into daily practice. The results of this study may serve as a reference for other schools in developing contextual P5 projects oriented toward character building.